Preparação de vidros e vitrocerâmicas no sistema SbPO4-PbO-ZnO dopados com manganês e ferro - Siqueira, Renata Fernandes (2014)
In the present research project a new glass composition containing SbPO4 ZnO PbO was obtained by melt quenching technique. After a brief study of the matrix, a composition was chosen and doped with MnO e Fe2O3 in quantities varying from 0 to 20 mol%. The next step was to perform a heat treatment above glass transition temperature in order to produce glass-ceramics from the obtained glasses. Then, the vitreous materials were characterized by thermal analysis (DSC), and the structural study of the materials was done using absorbance spectroscopy in the UV-vis-NIR and Raman, besides the electronic paramagnetic resonance (EPR) and fluorescence measurements. Refractive index was measured by M-Lines spectroscopy. The new materials were also characterized by X ray diffraction (XRD), optical microscopic and scanning (SEM) and transmission electronic microscopic (TEM). Finally, magnetic measurements were performed in a magnetic force microscope (MFM). The prepared glass samples have a high refractive index and thermal stability over 100 °C, which may be interesting for optical fiber synthesis. After addition of the paramagnetic metals (Mn, Fe), the thermal stability increased even more. The optical analysis of the manganese doped glasses showed that the ions are in the Mn2+ oxidation state, but after heat treatment the color of the glass changes since a small amount of the dopant cation is oxidized to Mn+3 and some magnetism characteristic may be observed. Even though the optical properties were not good with addition of manganese and iron, the sample showed a significant magnetic response. These results of magnetic analysis are promising for the advance of spin-photonics and may be suitable to design devices for information storage.